Early Results of Rotating Platform Total Knee Replacement - Arif, M.; Makundala, V.; Choon, D.S.K. (Malaysian Medical Association, 2005)
We report on our early experiences with the Press Fit Condylar Rotating Platform (PFC-RP) total knee replacement prosthesis at University Malaya Medical Centre. This new prosthesis was introduced to Malaysia in 2001. It combines the rotating platform technology of Low Contact Stress (LCS) and the modularity of Press Fit Condylar (PFC) system. We performed 18 knee replacements using cruciate retaining prosthesis without patellar resurfacing in 10 patients and followed them up over a period of 16-month. A new operative strategy was developed to match the flexion and extension gaps. The pre- and post-operative assessments were made according to the American Knee Society Scores (AKSS). Post-operative pain relief, range of motion, knee score and functional score showed promising early results. The average knee rating improved from 28 to 91 (range 75-94). Average functional assessment improved from 26 to 82 (range 75-90). The radiographic assessments show correction of an average pre-operative varus of 140 to post-operative valgus of 50 (range 4-70). Early infection occurred in two knees. Both responded to aggressive debridement and antibiotics. Stiffness was encountered in one patient. There were no spinouts of the insert. We are satisfied that the implants are performing well at the one-year mark and will continue monitor this cohort.